Determining the Distribution Route Using the Clustered Generalised Vehicle Routing Problem Model and Dijkstra's Algorithm - Awal Aflizal Zubir; Andriansyah Andriansyah; Salsabila Derisma (Journal of Science, Technology, and Visual Culture, 2022)
Distributions and logistics processes are the essential element activities integral to the industrial sector, one of them is the distribution of LPG 3 kg. The most common issue that occurs in the distribution process is determining the vehicle routes which are often called Vehicle Routing Problems. PT Amalia Yusri is one of the distributor agents of LPG 3 kg in Banda Aceh and also had the same issue to determine the distribution routes. The Clustered Generalized Vehicle Routing Problem model is used to determine the optimal distribution route on the vertex destinations that have been grouped. Based on the number of requests and vehicle capacity, the grouping and formation of clusters are divided into two days and split into five groups. The first day consists of group 1 and group 2; while on the second day are group 3, group 4, and group 5. The method that is used to optimise distribution distance is Dijkstra Algorithm. From the application of the CGVRP model and Dijkstra Algorithm obtained a total distance for group 1 is 25.582 m, group 2 is 24.650 m, group 3 is 39.350 m, group 4 is 27.500 m, and group 5 is 38.500 m.